Digital transformation: an overview of the phenomenon based on a dynamic capabilities framework - Albino, Raphael Donaire (2021)
This study investigates digital transformation, which is understood as the revolution promoted by digital technologies in an organization\'s strategy and work systems, generating a reformulation of pre-established business models, creating better interactions with customers and optimizing processes in order to produce favorable and sustainable financial outcomes. According to empirical data, only some organizations succeed in digital transformation and go beyond the initial change stages. Unrealistic expectations, lack of financial support, limited technology focus, poor governance and underestimate of cultural barriers are examples of failures throughout the digital transformation initiatives, particularly in organizations that established their business models in a pre-Internet environment. In view of such context, this study aims at analyzing definitions, challenges and explain digital transformation in the light of a framework based on the dynamic capabilities theory. Considering the complexity of the subject, this study was organized in three intertwined papers that used as methodological approaches the systematic literature review, the Design Science Research (DSR) and multiple case studies, respectively. The presented outcomes show that digital transformation is a phenomenon that can be explained from triggers, barriers, enablers and impacts on organizations. Elements, such as the review of an organization\'s value proposition, understanding different types of revenue models supported by the adoption of digital technologies, the silos strengthened by structures that are against changes, the executive support and data governance are examples of some of the components listed in this study to understand the digital transformation. In addition to the elements surrounding an organization, through the case studies and specialists\' opinions this study found out that practices that keep an organization connected with the external environment; the use of data to develop future strategies; the dissemination of a digital mindset; the agility to lead the strategy; the capacity to create digital products; the flexibility of the business model considering partnerships; the navigation through innovation ecosystems; the flexibility of internal structures and the improvement of digital maturity represent capabilities that, when developed internally, will cause organizations to generate a competitive advantage during digital transformation.